Method for improving stamping performance of TA1 pure titanium sheet through thermal oxidation treatment

By thermal oxidation treatment on the surface of TA1 pure titanium thin plate, an oxide film containing Ti6O and TiO2 was generated, which solved the problem of insufficient ductility of the titanium thin plate during stamping and forming, significantly improved stamping performance and reduced production costs.

CN119615048APending Publication Date: 2025-03-14PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411836406.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing titanium thin plates are insufficient in the multi-pass stamping process and are prone to rupture. The commonly used coating lubrication and stress-removing annealing processes are time-consuming and labor-intensive, and costly.

Method used

A layer of oxide film containing Ti6O and TiO2 was generated on the surface of the TA1 pure titanium thin plate by thermal oxidation, thereby improving the stamping performance of the thin plate. The specific steps include cutting the TA1 pure titanium thin plate to an appropriate size, heating it to 600-700°C in an air atmosphere, insulated for at least 30 minutes, and forming an oxide film.

Benefits of technology

After thermal oxidation treatment, the stamping performance of TA1 pure titanium thin plate is significantly improved, the surface friction coefficient is reduced, and the ductility is enhanced, which reduces the risk of cracking, avoids additional coating and stress-relieving annealing steps, and reduces production costs and time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005186819460000041
    Figure BDA0005186819460000041
  • Figure BDA0005186819460000051
    Figure BDA0005186819460000051
  • Figure BDA0005186819460000061
    Figure BDA0005186819460000061
Patent Text Reader

Abstract

The invention provides a method for improving the stamping performance of a TA1 pure titanium sheet through thermal oxidation treatment, which comprises the following steps of: blanking the TA1 pure titanium sheet with the grain size greater than or equal to 10 grade into a blank size required by part forming to obtain a sheet material; and the sheet material is placed vertically after being decontaminated, heating is conducted, the heating process comprises the steps that the temperature is increased to 600-700 DEG C from the room temperature, heat preservation is conducted for at least 30 min, and the treated pure titanium sheet is obtained. According to the method, an oxide layer is generated on the surface of the pure titanium sheet through surface thermal oxidation treatment at the temperature of 600-700 DEG C, and the stamping performance of the pure titanium sheet can be improved due to the double influences of structure changes and the oxide layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of non-ferrous gold sheet forming, and in particular relates to a method for improving the stamping performance of a TA1 pure titanium sheet through thermal oxidation treatment. Background Art

[0002] With the development of the application of pure titanium thin plates in the field of daily necessities, higher requirements are placed on the stamping performance of pure titanium thin plates, and most product production processes require multi-pass stamping forming. However, titanium thin plates manufactured by conventional methods often have insufficient ductility and breakage during the multi-pass stamping forming process. The commonly used method is to perform coating lubrication and stress relief annealing, which takes a lot of time and labor costs. Therefore, developing a method to improve the stamping performance of pure titanium thin plates has become a goal pursued by various companies and has received great attention. Summary of the invention

[0003] In view of this, the object of the present invention is to provide a method for improving the stamping performance of TA1 pure titanium thin plate by thermal oxidation treatment, which method can improve the stamping performance of TA1 pure titanium thin plate.

[0004] The present invention provides a method for improving the stamping performance of a TA1 pure titanium sheet by thermal oxidation treatment, comprising the following steps:

[0005] Cutting TA1 pure titanium thin plates with a grain size of ≥10 into the blank size required for part forming to obtain sheet materials;

[0006] After decontamination, the sheet is placed vertically and heated. The heating process includes: heating from room temperature to 600-700° C. and keeping the temperature for at least 30 minutes to obtain a treated pure titanium sheet.

[0007] Preferably, an oxide film containing Ti6O and TiO2 is formed on the surface of the pure titanium sheet during the heating process.

[0008] Preferably, the oxide film has a thickness of 0.2 to 2.0 μm.

[0009] Preferably, the heating rate from room temperature to 600-700° C. is 10-20° C. / min.

[0010] Preferably, the heated atmosphere is air.

[0011] Preferably, after cooling, the surface is coated with stamping lubricating oil and stamping is performed according to the stamping process.

[0012] Preferably, the grain size of the TA1 pure titanium sheet is level 10 or level 10.5.

[0013] Preferably, the temperature is raised from room temperature to 650-700°C.

[0014] Preferably, the thickness of the TA1 pure titanium sheet is 0.5 mm.

[0015] Preferably, the surface friction coefficient of the treated pure titanium sheet is 0.124-0.130.

[0016] The present invention provides a method for improving the stamping performance of TA1 pure titanium thin plate by thermal oxidation treatment, comprising the following steps: cutting TA1 pure titanium thin plate with a grain size of ≥10 into a blank size required for part forming to obtain a sheet; placing the sheet vertically after decontamination and heating it, wherein the heating process comprises: heating from room temperature to 600-700°C, and keeping the temperature for at least 30 minutes to obtain a treated pure titanium thin plate. The method generates an oxide layer on the surface of the TA1 pure titanium thin plate by thermal oxidation treatment at 600-700°C, and due to the dual effects of organizational changes and the oxide layer, the stamping performance of the pure titanium thin plate can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is an X-ray diffraction measurement diagram of the oxide film produced in Example 1 of the present invention. DETAILED DESCRIPTION

[0018] The present invention provides a method for improving the stamping performance of a TA1 pure titanium sheet by thermal oxidation treatment, comprising the following steps:

[0019] Cutting TA1 pure titanium thin plates with a grain size of ≥10 into the blank size required for part forming to obtain sheet materials;

[0020] After decontamination, the sheet is placed vertically and heated. The heating process includes: heating from room temperature to 600-700° C. and keeping the temperature for at least 30 minutes to obtain a treated pure titanium sheet.

[0021] The grain size of the TA1 pure titanium sheet used in the present invention is ≥ grade 10, preferably grade 10 to 11. In a specific embodiment, the grain size of the TA1 pure titanium sheet is grade 10 or grade 10.5. The thickness of the TA1 pure titanium sheet is 0.5 mm.

[0022] The present invention uses a cleaning agent to remove oil and dust on the surface of the sheet material under ultrasonic conditions. The cleaning agent used in the present invention is a cleaning agent well known to those skilled in the art.

[0023] The present invention places the sheet material vertically on a rack and puts it into a muffle furnace for heating; the purpose of placing it vertically is to enable the front and back sides of the sheet material to be oxidized evenly.

[0024] The heating process of the present invention is carried out in an air atmosphere. During the heating process, the pure titanium thin plate undergoes an oxidation reaction with oxygen to form a dense oxide film containing Ti6O and TiO2; the thickness of the oxide film is 0.2 to 2.0 μm. In a specific embodiment, the thickness of the oxide film is 0.7 μm, 0.9 μm, 0.8 μm or 1.2 μm.

[0025] The heating rate of the present invention from room temperature to 600-700°C is 10-20°C / min; preferably, the temperature is raised to 650-700°C; in a specific embodiment, the temperature is raised to 650°C or 700°C. As the temperature rises, the oxide film on the surface of the pure titanium sheet will also thicken, and interfere with the light, showing different colors; when the temperature is heated to 600-700°C, the color of the oxide layer is blue-gray. At this time, the oxide film not only protects the titanium surface, but also improves the surface roughness of the pure titanium sheet, especially reduces the difference in the surface roughness of the pure titanium sheet in the rolling direction and the transverse direction. The oxide film also plays a certain lubricant oil storage effect; in order to make the oxidation uniform, the present invention is kept warm for at least 30 minutes. After the thin plate is heated and oxidized, the titanium plate structure, yield strength ratio, elongation, friction coefficient, etc. are changed, thereby effectively improving the stamping performance of the pure titanium sheet.

[0026] After the heating process is completed, the present invention is furnace cooled or air cooled. After the sample is cooled, it can be observed that a blue-gray oxide layer has formed on the surface.

[0027] The present invention applies stamping lubricating oil to the surface after cooling, and performs stamping forming according to the stamping process; the stamping lubricating oil used in the present invention is selected from special stamping lubricating oil for titanium alloy (such as Kozer CUT-312 titanium alloy stretching oil); or L-AN100 for full loss system oil; or 95% L-AN46 type lubricating oil as a base, 5% castor oil as an oiliness agent uniform mixture; or 85% L-AN46 type lubricating oil as a base, 5% castor oil as an oiliness agent, 10% chlorinated paraffin as an extreme pressure agent uniform mixture. The lubricating oil used in the present invention is titanium alloy stamping lubricating oil; titanium alloy stamping lubricating oil is a commercially available commodity well known to those skilled in the art. The present invention applies lubricating oil to reduce the friction between the stamping process and the mold, which is more conducive to forming; during the metal stamping process, friction will be generated between the metal sheet and the mold. If there is no lubricant, the friction will cause scratches and wear on the surface of the metal sheet, affecting the product quality. Stamping oil can form a lubricating film between the metal sheet and the die, reducing friction, allowing the metal sheet to pass through the die smoothly and reducing energy loss.

[0028] The amount of lubricating oil applied is to evenly cover the surface of the sample, and the coating thickness depends on many factors, including the size and shape of the stamping part, the stamping process requirements, the friction coefficient of the die surface, etc. The present invention achieves the purpose of reducing cracking of pure titanium thin plates in multi-pass stamping by surface oxidation combined with the application of stamping lubricating oil, which is of great significance to the promotion and application of pure titanium thin plates.

[0029] The surface friction coefficient of the pure titanium thin plate treated by the above method of the present invention is 0.124-0.130; in a specific embodiment, the surface friction coefficient is 0.130, 0.125, 0.126 or 0.124.

[0030] The stamping process of the present invention does not require additional lamination and stress relief annealing steps.

[0031] The method provided by the present invention is applicable to TA1 pure titanium thin plates with normal rolling process available on the market, has good adaptability, is easy to operate, and can effectively improve the stamping performance of ordinary rolled TA1 (grain size ≥ grade 10) pure titanium thin plates.

[0032] In order to further illustrate the present invention, a method for improving the stamping performance of TA1 pure titanium thin plate by thermal oxidation treatment provided by the present invention is described in detail below in combination with embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0033] The titanium alloy special stamping lubricant used in the following embodiments is Kozer CUT-312 titanium alloy stretching oil.

[0034] Example 1

[0035] The 0.5mmTA1 (grain size 10) pure titanium sheet purchased from the market was selected, and 90mm×90mm cupping test specimens were cut. 18 specimens were divided into three groups (Group A, Group B and Group C) with 6 pieces in a group, and the mean difference of IE cupping value was compared. The process parameters of the test remained the same, and the surface was coated with titanium alloy stamping lubricant. The specimens in Group A were original plates, and only lubricant was applied for the test; the specimens in Group B were placed in a muffle furnace and heated to 700℃ at a heating rate of 10℃ / min for thermal oxidation treatment, and then cooled with the furnace after 30 minutes of heat preservation. The specimens after thermal oxidation treatment were coated with lubricant for the test; the specimens in Group C were placed in a muffle furnace and heated to 500℃ for blueing treatment, and then cooled with the furnace after 30 minutes of heat preservation. The specimens after blueing treatment were coated with lubricant for the test.

[0036] It was measured that the surface friction coefficient of the original plate of group A was about 0.138; the surface friction coefficient of group B oxidized at 700℃ for 30 minutes was about 0.124, and the thickness of the oxide layer was about 0.7μm; the surface friction coefficient of group C oxidized at 500℃ for 30 minutes was about 0.149, and the thickness of the oxide layer could not be measured because no complete oxide layer was generated.

[0037] X-ray diffractometer (XRD) can accurately determine the crystal structure of a sample, and can perform phase analysis, quantitative analysis, and qualitative analysis on the sample. It is a common method for characterizing the phase structure of materials. Its working principle uses characteristic X-rays with extremely short wavelengths and uses crystal materials as spatial diffraction gratings. When X-rays are incident on the crystal to be tested at different angles, the crystal planes that meet the Bragg diffraction conditions will be detected, generating an XRD diffraction pattern. By analyzing the XRD pattern, information such as the phase structure and lattice parameters of the material can be obtained. XRD qualitative analysis is to compare the diffraction patterns of the sample to be tested with those of the known phase. If the diffraction spectrum of the sample contains the spectrum of the known phase, it can be determined that the sample contains the phase. Figure 1 The X-ray diffraction measurement diagram of the oxide film generated by the sample of group B in Example 1 of the present invention; Figure 1 It can be seen that the generated oxide film contains Ti6O and TiO2.

[0038] Table 1

[0039]

[0040] As can be seen from Table 1, after the 0.5mm TA1 (grain size 10) pure titanium thin plate in Example 1 was subjected to 700℃ thermal oxidation and heat preservation for 30 minutes, its stamping performance was significantly improved, and the average cupping value increased by more than 0.8mm; while after 500℃ blueing and heat preservation for 30 minutes, the stamping performance was worse than that of the original plate.

[0041] Example 2

[0042] The 0.5mmTA1 (grain size 10) pure titanium sheet purchased from the market was selected, and 90mm×90mm cupping test specimens were cut. 18 specimens were divided into three groups (Group A, Group B and Group C) with 6 pieces in a group, and the mean differences of IE cupping values ​​were compared. The process parameters of the test remained the same, and the same composition lubricant was used. The specimens in Group A were original plates, and only lubricants were applied for the test; the specimens in Group B were placed in a muffle furnace and heated to 700℃ at a heating rate of 10℃ / min for thermal oxidation treatment, and then air-cooled after 1 hour of heat preservation. The specimens after thermal oxidation treatment were coated with lubricants for the test; the specimens in Group C were placed in a muffle furnace and heated to 500℃ for blueing treatment, and then air-cooled after 1 hour of heat preservation. The specimens after blueing treatment were coated with titanium alloy stamping lubricants for the test.

[0043] It was measured that the surface friction coefficient of the original plate of group A was about 0.138; the surface friction coefficient of group B oxidized at 700℃ for 1 hour was about 0.126, and the thickness of the oxide layer was about 0.9μm; the surface friction coefficient of group C oxidized at 500℃ for 1 hour was about 0.146, and the thickness of the oxide layer could not be measured because no complete oxide layer was generated.

[0044] Table 2

[0045]

[0046] As can be seen from Table 2, after the 0.5 mm TA1 (grain size 10) pure titanium thin plate in Example 2 was subjected to thermal oxidation and heat preservation treatment at 700°C for 1 hour, its stamping performance was significantly improved, and the average cupping value increased by more than 0.6 mm; while after being subjected to blueing and heat preservation treatment at 500°C for 1 hour, the stamping performance was worse than that of the original plate.

[0047] Example 3

[0048] The 0.5mmTA1 (grain size 10.5 grade) pure titanium sheet purchased from the market was selected, and 90mm×90mm cupping test specimens were cut. 18 specimens were divided into three groups (Group A, Group B and Group C) with 6 pieces in a group, and the mean differences of IE cupping values ​​were compared. The process parameters of the test remained the same, and the same composition lubricant was used. The specimens in Group A were original plates, and only lubricants were applied for testing; the specimens in Group B were placed in a muffle furnace and heated to 700℃ at a heating rate of 10℃ / min for thermal oxidation treatment, and then cooled with the furnace after 30 minutes of heat preservation. The specimens after thermal oxidation treatment were coated with lubricants for testing; the specimens in Group C were placed in a muffle furnace and heated to 500℃ for blueing treatment, and then cooled with the furnace after 30 minutes of heat preservation. The specimens after blueing treatment were coated with titanium alloy stamping lubricants for testing.

[0049] The surface friction coefficient of the original plate in group A is about 0.140; the surface friction coefficient of group B oxidized at 700℃ for 30 minutes is about 0.125, and the thickness of the oxide layer is about 0.8μm; the surface friction coefficient of group C oxidized at 500℃ for 30 minutes is about 0.150, and the thickness of the oxide layer cannot be measured because a complete oxide layer is not generated.

[0050] Table 3

[0051]

[0052] As can be seen from Table 3, after the 0.5 mm TA1 (grain size 10.5 grade) pure titanium thin plate in Example 3 was subjected to thermal oxidation and heat preservation at 700°C for 30 minutes, its stamping performance was significantly improved, and the average cupping value increased by more than 1.0 mm; while after being subjected to blueing and heat preservation at 500°C for 30 minutes, the stamping performance was worse than that of the original plate.

[0053] Example 4

[0054] The 0.5mmTA1 (grain size 10.5 grade) pure titanium sheet purchased from the market was selected, and 90mm×90mm cupping test specimens were cut. 18 specimens were divided into three groups (Group A, Group B and Group C) with 6 pieces in a group, and the mean differences of IE cupping values ​​were compared. The process parameters of the test remained the same, and the same composition lubricant was used. The specimens in Group A were original plates, and only lubricants were applied for the test; the specimens in Group B were placed in a muffle furnace and heated to 650℃ at a heating rate of 10℃ / min for thermal oxidation treatment, kept warm for 2 hours and then air-cooled, and the specimens after thermal oxidation treatment were coated with lubricants for the test; the specimens in Group C were placed in a muffle furnace and heated to 500℃ for blueing treatment, kept warm for 2 hours and then air-cooled, and the specimens after blueing treatment were coated with titanium alloy stamping lubricants for the test.

[0055] The surface friction coefficient of the original plate of group A is about 0.140; the surface friction coefficient of group B oxidized at 700℃ for 2 hours is about 0.130, and the thickness of the oxide layer is about 1.2μm; the surface friction coefficient of group C oxidized at 500℃ for 2 hours is about 0.144, and the thickness of the oxide layer cannot be measured because a complete oxide layer is not formed.

[0056] Table 4

[0057]

[0058] It can be seen from Table 4 that after the 0.5 mm TA1 (grain size 10.5 grade) pure titanium thin plate in Example 1 was subjected to 650°C thermal oxidation and heat preservation for 2 hours, its stamping performance was significantly improved, and the average cupping value increased by more than 1.0 mm; while after 500°C blueing and heat preservation for 2 hours, the stamping performance was worse than that of the original plate.

[0059] It can be seen from the above embodiments that the present invention provides a method for improving the stamping performance of TA1 pure titanium thin plate by thermal oxidation treatment, comprising the following steps: cutting TA1 pure titanium thin plate with a grain size ≥10 into the blank size required for part forming to obtain a sheet; placing the sheet vertically after decontamination and heating it, and the heating process includes: heating from room temperature to 600-700°C, keeping warm for at least 30 minutes, and obtaining a treated pure titanium thin plate. This method generates an oxide layer on the surface of the pure titanium thin plate by thermal oxidation treatment at 600-700°C, and improves the stamping performance of the pure titanium thin plate due to the dual effects of organizational changes and the oxide layer.

[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for improving the stamping performance of TA1 pure titanium sheet by thermal oxidation treatment, comprising the following steps: Cutting TA1 pure titanium thin plates with a grain size of ≥10 into the blank size required for part forming to obtain sheet materials; After decontamination, the sheet is placed vertically and heated. The heating process includes: heating from room temperature to 600-700° C. and keeping the temperature for at least 30 minutes to obtain a treated pure titanium sheet.

2. The method according to claim 1, characterized in that During the heating process, a mixed oxide film containing Ti6O and TiO2 is formed on the surface of the pure titanium sheet.

3. The method according to claim 2, characterized in that The thickness of the oxide film is 0.2 to 2.0 μm.

4. The method according to claim 1, characterized in that The heating rate from room temperature to 600-700°C is 10-20°C / min.

5. The method according to claim 1, characterized in that The heating atmosphere is air.

6. The method according to claim 1, characterized in that After cooling, the surface is coated with stamping lubricant and stamping is carried out according to the stamping process.

7. The method according to claim 1, characterized in that The grain size of TA1 pure titanium sheet is level 10 or level 10.

5.

8. The method according to claim 1, characterized in that Raise the temperature from room temperature to 650-700°C.

9. The method according to claim 1, characterized in that: The thickness of TA1 pure titanium sheet is 0.5mm.

10. The method according to claim 1, characterized in that The surface friction coefficient of the treated pure titanium sheet is 0.124-0.130.